Analysis of Financial Management in Economic Empowerment of MSMEs: A Case in a Tourism Village - Latif, Imam Nazarudin; Heriyanto, Heriyanto; Mardiana, Mardiana; Dewi, Catur Kumala (Universitas Negeri Semarang, 2023)
Rural economic development requires quick and appropriate action to maximise existing resources in the village through an entrepreneurial movement. One solution is to build a Tourism Village, which will increase the role of Micro, Small, and Medium Enterprises (MSMEs) around the area. Therefore, it is very important for MSMEs to have good financial management in order to improve their business performance. This study aims to identify and evaluate the level of effectiveness of financial management in MSMEs in Kampung Ketupat, Jalan Mangkupalas, Kelurahan Mesjid, Samarinda Seberang, Samarinda City, East Kalimantan. The method used in this research is qualitative through observation and interviews with key informants in Kampung Ketupat. The results showed that the financial management of MSMEs in Kampung Ketupat is based on a system of capital assistance, joint venture and profit sharing through PKK. This system is said to be effective because it fulfils the Empowerment index, which is an index that assesses the level of empowerment of MSMEs. The Empowerment Index provides a broad view of the effectiveness of MSME empowerment and can be used as a reference to determine steps to strengthen MSME performance, especially in terms of financial planning, implementation, and control. Therefore, good financial management in MSMEs will provide great benefits for the performance and sustainability of MSMEs in Kampung Ketupat. This research contributes to the scientific world, especially regarding the study of financial management of MSMEs in Kampung Ketupat on Jalan Mangkupalas, Mesjid Village, Samarinda Seberang, Samarinda City, East Kalimantan.